sec²(90° – Theta) + tan²(90° – Theta)
= cosec²0 + cot²
Prove
Answers
Answered by
1
Answer:
Step-by-step explanation:
Sec(90-Φ)=cosecΦ......................(1)
secΦ= Cosec
Φ
Tan(90-Φ)= CotΦ...........................(2)
Tan(90-Φ) =cot
Φ
(1)+(2)
== secΦ+Tan
(90-Φ) =Cosec
Φ +cot
Φ
Answered by
2
Answer:
to prove:
sec²(90°–Φ)+tan²(90°–Φ)
sec(90–Φ)=cosec Φ
tan (90–Φ)=cotΦ
so.... by using the identities.
putting the values of these. and, then we get
=cosec²Φ+cot²Φ
proved...
Step-by-step explanation:
hope this help u....
mark as brainliest answer..
follow me.....
thanks!!!!
Similar questions